2022
DOI: 10.3389/frsus.2022.1057190
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of Power-to-X derived dimethyl ether using the sorption enhanced DME synthesis process

Abstract: Dimethyl ether (DME) could have a promising future as a sustainable diesel fuel replacement as it requires only relatively minor engine modifications. It can be produced from renewable H2 and captured CO2 using Power-to-X technologies. To gain support through the EU Renewable Energy Directive, the production and use of CO2-derived DME as a fuel needs to produce emission savings of at least 70% over the petrodiesel alternative. This study assesses the carbon footprint of producing DME via the sorption-enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Styring et al have shown that the sorption-enhanced DME synthesis (SEDMES) process can reduce the carbon footprint by 77% when using DME as an alternative to petrodiesel, considering the use of offshore wind H 2 . 203 However, the carbon footprint can be reduced up to 90% if waste heat and renewable energy-assisted CO 2 capture are implemented in DME production. Tomatis et al have suggested that replacing petrodiesel with pure DME reduces greenhouse gas emissions by 72% while blending DME with petrodiesel (15%) results in a smaller reduction in greenhouse gas emissions.…”
Section: Process Engineering Techno-economic and Environmental Impactmentioning
confidence: 99%
See 1 more Smart Citation
“…Styring et al have shown that the sorption-enhanced DME synthesis (SEDMES) process can reduce the carbon footprint by 77% when using DME as an alternative to petrodiesel, considering the use of offshore wind H 2 . 203 However, the carbon footprint can be reduced up to 90% if waste heat and renewable energy-assisted CO 2 capture are implemented in DME production. Tomatis et al have suggested that replacing petrodiesel with pure DME reduces greenhouse gas emissions by 72% while blending DME with petrodiesel (15%) results in a smaller reduction in greenhouse gas emissions.…”
Section: Process Engineering Techno-economic and Environmental Impactmentioning
confidence: 99%
“…Styring et al have shown that the sorption-enhanced DME synthesis (SEDMES) process can reduce the carbon footprint by 77% when using DME as an alternative to petrodiesel, considering the use of offshore wind H 2 203. However, the carbon footprint can be reduced up to 90% if waste heat and renewable energy-assisted CO 2 capture are implemented in DME production.…”
mentioning
confidence: 99%